KAJIAN ASPEK DEMOGRAFI, SOSIAL, DAN EKONOMI PARTISIPASI TENAGA KERJA WANITA DI PABRIK KAYU LAPIS - Setiasih Irawanti; Mieke Suharti; I M Sulastining (Jurnal Penelitian Hasil Hutan, 1994)
Plywood industry (wood based industry) is a suitable accupation  field  for woman labor, where woman can participate in forestry development.                                                                The  aim  of  the  study  is  to  evaluate participation of  woman  labor  at plywood  industry  by  observing  their  activities from demographical, social and economical aspects.This  study  was  conducted  by  collecting  data from  plywood  companies, Provincial    Forestry  Office,  Statistics  Office,  and interviewing 10 percent of woman and man labors from plywood companies in East Kalimantan province.The results show that about 74 percent of production  labor is woman, and most of them work in all sections such as veneer matching and splicing, gluing, pressing,  and finishing. About 70 percent of woman labor is unmarried, average age is 24 years  with high school education, so they have adequate capacity to work.  About 60 percent comes from  out of East Kalimantan province. It shows that woman labor at plywood  industry has high motivation and mobility to  work.  Generally, they live in a rent house  with minimum condition for their welfare.  They usually do not have much time left to participate in social activities commonly organized in surrounding living area.Basic salary of woman labor working for normal shift is  Rp.  2,500 and for long shift is Rp. 3,300 per day.  It means higher than Minimum Regional Salary determined by  goverment office. Woman labor gross income working for normal shift is Rp.  135,000 per month in average  or more   than Minimum Physical Need of unmarried labor that is only Rp. 86.930,-. While the gross income for those working for  long shift is Rp.  242,500 per month or more than Minimum Physical Need  for one family consisting of a pair of parents having a child which is only Rp.200,685,-. In conclusion, woman labor  income can give a